2020
DOI: 10.1186/s12874-020-01088-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting adolescents’ participation in randomized controlled trials evaluating the effectiveness of healthcare interventions: the case of the STEPSTONES project

Abstract: Background: Recruitment of adolescents to intervention studies is a known challenge. For randomized controlled trials (RCT) to be generalizable, reach must be assessed, which means ascertaining how many of the intended population actually participated in the trial. The aim of this study was to evaluate the reach and representativeness of an RCT evaluating the effectiveness of a complex intervention for adolescents with chronic conditions. Methods: A mixed methods sequential explanatory design was employed. Fir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In a previous study, 43% of adolescent participants who met the diagnostic criteria for moderate to severe depression suggested that helping others and contributing to wider understanding was their main motivation for participating in a randomised clinical trial [ 56 ]. Similarly, Saarijärvi et al, [ 57 ] found adolescents with more complex conditions felt grateful towards research and the healthcare system and were thus motivated to ‘give back’. A population with a specific common interest (e.g., a medical condition) could potentially have more altruistic motivations.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, 43% of adolescent participants who met the diagnostic criteria for moderate to severe depression suggested that helping others and contributing to wider understanding was their main motivation for participating in a randomised clinical trial [ 56 ]. Similarly, Saarijärvi et al, [ 57 ] found adolescents with more complex conditions felt grateful towards research and the healthcare system and were thus motivated to ‘give back’. A population with a specific common interest (e.g., a medical condition) could potentially have more altruistic motivations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, only a third of adolescents in the transition program participated during the information day. Potential reasons for this are that adolescents with a CC might feel uncomfortable in engaging with others in the same situation and spend excessive time thinking about their illness [ 29 , 30 ]. Within patient empowerment, the ability to enable others is a core construct [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several participants did not attend the information day due to feeling uncomfortable about interacting with other adolescents’ with CHD. Previous studies have shown that adolescents lack of engagement in their illness affects study participation negatively [ 15 ]. In addition, group dynamic and not being able to identify with the role models during the information day were seen as shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative explorative design was employed. This study was part of a larger process evaluation study [ 11 , 15 ]. The planning and reporting of this study followed the Consolidated Criteria for Reporting Qualitative studies (COREQ) checklist [ 16 ] (Additional file 1 ).…”
Section: Methodsmentioning
confidence: 99%